2016
DOI: 10.3168/jds.2016-11116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between type and test-day milk yield in small dual-purpose cattle populations: The Aosta Red Pied breed as a case study

Abstract: This study aimed at estimating the relationships between linear type traits and milk production in the dual-purpose Aosta Red Pied (ARP) cattle breed, by expressing type traits as factor scores with the same biological meaning of the individual traits. Factor analysis was applied to individual type traits for muscularity and udder of 32,275 first-parity ARP cows, obtaining 3 factor scores for individual muscularity (F1), udder side (F2), and udder conformation (F3). Data from 169,008 test-day records of milk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 53 publications
7
17
1
1
Order By: Relevance
“…In the present study, the heritability estimates of both PC and factors obtained were in agreement with the estimate of the heritability of the composite traits with PC1 and F1 (BC) showing the highest heritability and PC4 and F4 (FL) with the lowest estimate. These results are in accordance with the report of Mazza et al (2016a,b) where similar findings were disclosed for both individual traits and the multivariate techniques used in this study and this affirmed the possible use of both PCA and FA in animal breeding (Macciotta et al, 2012;Mazza et al, 2016b).…”
Section: Pca and Fasupporting
confidence: 94%
“…In the present study, the heritability estimates of both PC and factors obtained were in agreement with the estimate of the heritability of the composite traits with PC1 and F1 (BC) showing the highest heritability and PC4 and F4 (FL) with the lowest estimate. These results are in accordance with the report of Mazza et al (2016a,b) where similar findings were disclosed for both individual traits and the multivariate techniques used in this study and this affirmed the possible use of both PCA and FA in animal breeding (Macciotta et al, 2012;Mazza et al, 2016b).…”
Section: Pca and Fasupporting
confidence: 94%
“…Fontina cheese (FC), a PDO product, is manufactured from fullfat and unpasteurised ARP milk, from LO or HI pastures, within 2 h after every single morning and evening milking (Mazza et al 2016). For this purpose, milk from 47 ARP cows was repeatedly sampled from May to July, including both LO to HI pastures.…”
Section: Introductionmentioning
confidence: 99%
“…PCA has been widely used in animal production in order to understand the relationship between several traits that are of economic interest, and to understand the contribution of each trait in each PC [13][14][15][16][17][18][19][20][22][23][24][25][26][27]57,58]. In this study, we verified that the first six PCs explained 82.14% of the total variance, and the importance of each body measurement in the composition of these six PCs were determined by the correlations between the original variables and PCs, such as their weighting coefficients ( Table 2).…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, the selection of animals while considering the association between body morphometric traits and productive/reproductive traits can be effective for obtaining suitable biotypes for each production system. Research has shown the association between biotypes, and productive and reproductive traits [3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, there are limited studies examining functional biotype and their relationship with productive/reproductive in the buffalo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation